Familial Cutaneous Collagenoma - Ramchandra S; Sayal S K; Matety A R; Malik A K (Wolters Kluwer Medknow Publications, 1999)
Two cases of familial cutaneous collagenoma are presented for its rare occurrence. Histopathological report helped to establish the diagnosis.